Analisis Wacana pada Novel Mata di Tanah Melus karya Okky Madasari dengan Pendekatan Mimetik - Sadida, Sabila; Anggraini, Shintya Dwi; Arochman, Taufik (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
Literary work is seen as a work created by the author by imitating or representing real life. This is in accordance with the focus of literary studies using the mimetic approach which emphasizes the study of the relationship between a literary work and the life that exists outside the literary work. This research aims to 1) understand the novel Mata di Tanah Melus using the mimetic approach 2) analyze the relationship between the novel Mata di Tanah Melus and real life or actual life in Belu Regency, East Nusa Tenggara 3) analyze the phenomena and intrinsic elements in the novel that are related to the real life of the people of Belu, East Nusa Tenggara. The research method used was a descriptive qualitative method or research method that utilizes qualitative data and then described descriptively. The object of this research was dialog quotes and narratives in the novel Mata di Tanah Melus. The results of this study are that there are several parts of the novel Mata di Tanah Melus whose life is exactly the same as real life in Belu Regency, East Nusa Tenggara.